Use of vaginal dilators and effects on vaginal volume and quality of life: a randomized clinical trial - Natalia Carion Haddad; Marco Aurelio Pinho de Oliveira; Leila Cristina Soares (Fisioterapia e Pesquisa)
ABSTRACT Although it is advised to use vaginal dilators following radiotherapy to prevent vaginal stenosis, compliance is frequently low. This study aimed to assess adherence to the use of vaginal dilators after brachytherapy and its effects in women who received phone call or texting apps guidance. A total of 30 women who previously underwent brachytherapy for cervical cancer were randomized into two groups using the R program: monitoring via phone calls and monitoring via text messages. They underwent gynecological examination with measurement of vaginal volume and answered the Functional Assessment of Cancer Therapy-Cervix Cancer (FACT-CX) questionnaire at the initial consultation and at the sixth month. No association was found between adherence and the types of follow-up (p=0.79). In the first month, 43.3% adhered to dilators, 36.6% did so in the third month, and 23% in the sixth month. The highest adherence group had higher difference in vaginal volume scores (16.81±10.45 cm3) compared to the nonadherence group (10.45±9.55 cm3) with a strong effect size (d=1.68). The difference between the initial and final vaginal volume was not associated with the FACT-CX scores (rho=−0.369; p=0.08. Although no differences were observed in adherence to dilators and type of follow-up, high adherence demonstrated a direct effect on increasing vaginal volume, showing the need to promote educational forms that encourage adherence.